An Art of Nothing, an Art of Something: The Local in the Global or the Global in the Local?. Issue 1 (2nd January 2023) - Streak, Greg
Abstract : The solo exhibition, Nothing Matters, was installed on the mezzanine floor of an industrial panel beater warehouse at 400 Sydney Road, Durban, South Africa. The exhibition was open to the public from September-December 2021. The objective of the exhibition was to create 'something' of conceptual and aesthetic compulsion from a language of nothingness, whether it is 'found' in the surrounding temper of the public space or, in art, in various manifestations of the 'dematerialised object': the void; the empty canvas or gallery; the 'invisible' work; or the detritus of the everyday? The following is a dialogue between literary critic Michael Chapman and artist Greg Streak regarding the exhibition.